1997
DOI: 10.2307/3579606
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, Low-Level Exposure of Mice Prone to Mammary Tumors to 435 MHz Radiofrequency Radiation

Abstract: The purpose of this study was to determine if chronic, low-level exposure of mice prone to mammary tumors to 435 MHz radiofrequency (RF) radiation promotes an earlier onset, a faster growth rate or a greater total incidence of mammary tumors than in sham-exposed controls. Two hundred female C3H/HeJ mice were exposed for 21 months (22 h/day, 7 days/week) to a horizontally polarized 435 MHz pulse-wave (1.0 micros pulse width, 1.0 kHz pulse rate) RF radiation environment with an incident power density of 1.0 mW/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…Results reviewed here also show that long term, low level exposure ( 4 W/kg) to RF energy did not affect survival adversely [Chou et al, 1992;Liddle et al, 1994;Toler et al, 1997;Frei et al, 1998a,b;Adey et al, 1999Adey et al, , 2000Heikkinen et al, 2001;Zook and Simmens, …”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Results reviewed here also show that long term, low level exposure ( 4 W/kg) to RF energy did not affect survival adversely [Chou et al, 1992;Liddle et al, 1994;Toler et al, 1997;Frei et al, 1998a,b;Adey et al, 1999Adey et al, , 2000Heikkinen et al, 2001;Zook and Simmens, …”
Section: Discussionsupporting
confidence: 59%
“…Four studies using the mouse mammary model in long term, low level exposure studies did not observe any effect of RF exposure on cancer development [Toler et al, 1997;Frei et al, 1998a,b;Jauchem et al, 2001]. In an experiment, similar to the lung cancer colony assay by Szmigielski et al [1982] in which sarcoma cells were injected into mice, Santini et al [1988] injected melanoma cells into mice and found no effect of either CW or PW fields (2450 MHz) at 1.2 W/kg on cancer development.…”
Section: Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…After histopathological examination of the thymus, lymph nodes (if enlarged), spleen, liver, lung, kidney, adrenal, large and small bowel, urogenital system, eyes, brain, and any tissue appearing abnormal at autopsy, no mention was made of any observation of RF induced tissue necrosis. Toler et al [1997] exposed female mammary cancer prone mice to a 435 MHz signal, pulse wave, with a 1.0 ms pulse width at a 1.0 kHz pulse repetition rate. The SAR reported was 0.32 W/kg.…”
Section: In Vivo Correlates Of the Absence Of Rf Induced Cell Deathmentioning
confidence: 99%